Analysis of kinematic and anthropometric variables of the spike execution technique of volleyball - Kumar, R.; Kumar, A. (International Journal for Research in Applied Sciences and Biotechnology, 2020)
The research aimed to analyzed the kinematic and anthropometric variables of the spike execution technique of volleyball. 36 junior India level players from all over India of 16 - 20 years, age group were to be selected as subjects for the study. Purposive sampling technique was used for the selection of subjects. Participants were required to deliver five relevant spiked execution attempts as well as the perfect trial used for the analysis. Elite coaches who were available during the evaluation for grading. The moment execution of the spike was measured based on certain criteria (10 point system). A Go Pro Hero 5 (camera) with a frequency of 240 frames per second was placed on the sagittal plane to measure kinematic parameters. Based on sequence photographs the scholar developed stick figures from which selected biomechanical variables were calculated. The stick figures, angle of different joints, the center of gravity were developed by kinovea version 0.8.27 software. Body segments (i.e., standing height, upper arm, lower arm, palm length, upper leg, and lower leg length) were measured by the anthropometric kit. The multiple regression analysis was to be used to find out the prediction of kinematic & anthropometric variables of the spike execution technique of volleyball at 0.05 level of significance. Results of this study shows the value of R2 is 0.883 in selected kinematic variables and 0.119 in selected anthropometric variables. It may be interpreted that all the four kinematic variables selected in the model namely, angle at right wrist, angle at right elbow, angle at right shoulder, and ball velocity and the anthropometric variable selected in the model name, palm length have significant predictability in estimating the value of the moment execution technique of spike in volleyball. The result concluded that the kinematic variables i.e., ball velocity, angle at right wrist, angle at right elbow, angle at right shoulder and palm length in anthropometric measurement are contributed in the moment execution to creat a maximum speed, force and accuracy in the spike technique of volleyball. This study also contributed in the best way to execute the technique of spike for performance enhancement of volleyball players. It is suggested that the results of this study provide useful information for coaches to training in upper body strength & flexibility levels for attempting to increase range of joint movement, hiting with accuracy of the spike technique and its helps in injury prevention of volleyball players.